IMPLEMENTATION OF HOSPITAL INPATIENT ROOM DESIGN THAT SUPPORTS THE HEALING PROCESS - Wulandari, Rosdiana; Permana, Asep Yudi (Program Studi Arsitektur S-2 Universitas Pendidikan Indonesia, 2023)
Hospitals as health facilities need to be supported in all aspects. The healing factors obtained from health services do not stand alone but must be supported by physical health facilities to make the healing process more comprehensive. Many rules must be applied in hospitals and many aspects must be taken into account when designing a hospital, so designers must understand how to design according to standard rules and also aspects of user needs because healing is carried out through the physical and psychological aspects of the patient to encourage a more effective healing process. With the various facilities in hospitals, the role of inpatient rooms is often not a priority compared to service-based health facilities such as the emergency room, operating room, ICU room, and hemodialysis room which are important priorities. Even though the healing process takes the longest time in the inpatient room. It is felt that the current arrangement of inpatient rooms does not support the healing process. Therefore, this paper aims to guide designing inpatient rooms that truly meet the behavioral needs of residents so that it is hoped to create an inpatient room that encourages healing (healing environment). The method applied is descriptive qualitative by studying it based on the theory of architectural behavior architectural psychology, namely a Healing Environment that is suitable for hospitals through analysis of behavior that produces a need for space elements. Observe the condition of the inpatient room and the expected behavior of the occupants. The results of the analysis of inpatient rooms will be in the form of guidelines for designing inpatient rooms comprehensively. How to choose colors, choose finishing materials, furniture, and other necessary elements. The author hopes that this article can be used by all parties who will design, renovate, or carry out further research regarding inpatient room design. For designers, hospital owners, and hospital management throughout Indonesia, so whatever hospital class, location, government-owned, private, or foundation can apply hospital room design well.keywords: inpatient room, Healing Environment, Interior Design